A report from the WPA Working Group on Providing Mental Health Care for Migrants and Refugees - Schouler-Ocak, Meryam; Kastrup, Marianne C.; Kuey, Levent; Minas, Harry; Rataemane, Solomon; Rohlof, Hans; Lewis-Fernandez, Roberto (Wiley, 2024)
[Abstract Not Available]
Keywords: Action Plan 2020-2023; Implementation